Derivation and assessment of the opioid use disorder severity scale: prediction of health, psychological and social adjustment problems. (1st November 2020) - Kirisci, Levent; Tarter, Ralph E.; Reynolds, Maureen; Hayes, Kaleen N.; Cochran, Gerald; Vanyukov, Michael
ABSTRACT: Background: Severity of substance use disorder (SUD) is typically evaluated by tabulating the number of symptoms. The resulting estimate of disorder severity is, however, biased due to intercorrelations among symptoms and their unequal salience. Objective . Employing item response theory (IRT) methodology, opioid use disorder symptoms were calibrated to derive the Opioid Use Disorder Severity Scale (OUDSS) and assess its predictive ability in men and women separately. Methods: A two-parameter IRT model was utilized to derive the OUDSS from DSM-IV symptoms recorded on the Structured Clinical Interview for DSM-IV (SCID) in 438 men and 429 women who reported at least one lifetime opioid consumption event. The predictive ability of the OUDSS was evaluated using the 10 health, psychological, and social adjustment domains of the revised Drug Use Screening Inventory ( DUSI-R ) assessed 2 years later. Results: The OUDSS score predicted the severity of problems in all 10 DUSI-R domains in men and women. The OUDSS also predicted the DUSI-R diagnostic cutoff score of overall problem density score in men and women (OR = 2.21 and OR = 4.83, respectively). Withdrawal was the most frequently endorsed symptom in this sample of opioid users. The other symptoms' frequencies, while somewhat lower than withdrawal's, did not differ from it substantially, indicating a similar severity threshold. Conclusions: OUDSS enables dimensional measurement of opioid use severity on an interval scale. The OUDSS and DUSI-R together can identify problem areas requiring prevention or treatment.